Respiratory muscle endurance training with normocapnic hyperpnea improves ventilatory function and exercise performance in triathletes - Bernardi, E.; Melloni, E.; Pomidori, L.; Mandolesi, G.; Cogo, A. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Recent studies show that RMET reduces dyspnea perception, improves endurance performance and decreases ventilation during exercise (Verges, 2008). At the best of our knowledge no information about the changes of oxygen consumption (VO2) and ventilation (VE) during incremental test is available in healthy subjects after RMET. Aim: To evaluate the effect of 5 weeks of RMET with NH by means of Spirotiger on respiratory function, cycling and running performance in triathletes. Materials and Methods: 15 M triathletes were randomly allocated to 2 groups: RMET (10 subjects; age 28 ± 6) and control (5 subjects; age 29 ± 4) group. At baseline (T0) all subjects underwent: pulmonary function tests (forced expiratory volume in first second, FEV1; forced vital capacity, FVC; maximal inspiratory pressure, MIP; maximal voluntary ventilation, MVV) and exercise tests (maximal incremental and endurance cardiopulmonary tests performed with both cycle ergometer and treadmill). Then, RMET group trained at home for 5 weeks: 20 min daily, with Spirotiger, at the same ventilation level measured at the respiratory compensation point (roughly corresponding to 50% of MVV) during incremental test. The same tests were repeated after 5 weeks (T1). Between T0 and T1 all subjects maintained the same level of daily physical activity. Result: No change was found in control group (data not reported). In RMET group MIP (T0: 93±29; T1: 97±25 cmH2O*) and MVV (T0: 213±17; T1: 231±18 l/min*) significantly increased. No differences were found in FEV1 and FVC. Incremental test: maximum watt on cycle ergometer (T0: 389±106; T1: 429±119 watt*) and maximum speed on treadmill (T0: 18±2; T1: 19±2 Km/h*) significantly increased. The trend of VO2, VE and respiratory rate (RR) showed values significantly lower after RMET (p<0,05, ANOVA test). The dyspnea Borg score during endurance tests on treadmill (T0: 7,2/10; T1: 6,5/10*) and on cycle ergometer (T0: 7,3/10; T1: 6,7/10*) showed a significant lower score. No differences were found in ventilatory pattern during both endurance tests. After RMET a significantly lower weight (-1 Kg*) was measured. (* p<0,05; T test) Conclusion: RMET significantly improves MIP and MVV in triathletes and increases exercise performance during incremental test. Furthermore the VE becomes more efficient as shown by the reduction of VE and RR during incremental test and by the lower dyspnea Borg score.